The trials and tribulations of JTH Inc. Issue 2 (30th March 2019) - Jaiswal, Mayank; Maxwell, Robert
Abstract : Theoretical basis: The theoretical linkages are with dynamic nature of PESTEL analysis, Porter's five forces, resource-based view of the firm and characteristics of an entrepreneur. Research methodology: The names of the institutions and individuals involved have been disguised. However, the material facts of the case are authentic. Case overview/synopsis: This case discusses strategy in the context of a crisis situation in a small business. JTH Inc. was a computer subcontract manufacturing (SCM) firm serving the New England region of the USA. The influx of international competition (mainly from China) due to recession led to significant challenges for JTH and the SCM industry. JTH was struggling and the situation was further complicated by the founder's (Robert Maxwell) personal and emotional situation. Robert had to decide whether to keep the business running, close it down, merge with/be acquired by a competitor, innovate the business model or do something else. Complexity academic level: This case is designed to target undergraduate students of Strategic Management; it may also include Entrepreneurship students. It should most probably be taught in the first half of the course after concepts such as PESTEL, Porter and resource-based view of the firm have been taught.